PEMBINAAN KOMPETENSI SISWA PADA MATA PELAJARAN MATEMATIKA DI MTs MUHAMMADIYAH NUSA PUAN DESA BUANO UTARA - Ratau, Asria; Bugis, Halima; Hasani, Nurfadila; Sayang, Arien; Alwi, Ahmad; Borut, Ismail; Wagola, Wa Yati; Selan, Sehat; Samaneri, La Ahmat Yudin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Pattimura, 2025)
Mastery of basic competencies in Mathematics is a crucial aspect that supports students' academic success. However, field observations indicate that students' ability to understand mathematical concepts remains relatively low, which negatively affects their learning outcomes. This community service activity aims to provide guidance to students at MTs Muhammadiyah Nusa Puan, Buano Utara Village, in order to enhance their competence in Mathematics through a contextual learning approach. The implementation methods include the delivery of learning materials, question-and-answer sessions, group discussions, and evaluation through pre-tests and post-tests. The results of the activity show a significant improvement in students’ understanding of mathematical material, both in terms of learning motivation and critical thinking skills in solving mathematical problems. Thus, competence development through a contextual approach has proven to make a tangible contribution to improving the quality of mathematics learning in schools.